Obesity in pregnancy: maternal and perinatal outcome - Gupta, Aishwarya V.; Mehta, Ami; Patel, Bhargav; Mehta, Karan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this study was to find out the spectrum of complications during pregnancy due to maternal obesity with incidence and to assess the neonatal outcome. Methods: Retrospective study of antenatal patients was done in Sardar Vallabhbhai Patel Institute of Medical Sciences and Research (SVPIMSR), Ahmedabad from June 2019 to December 2019. Antenatal patients were categorized into 3 classes based on body mass index (BMI): class I=30-34.9 kg/m2, class II=35-39.9 kg/m2, and class III ≥40 kg/m2. The maternal and perinatal outcome of the patients was evaluated in relation to BMI. Results: A total of 61 women were included in the study, with 44 belonging to class I, 15 women to class II and 2 women to class III. In class I, 27% women had pre-eclampsia and its incidence increased with class II (69.2%) and class III (100%). The incidence of gestational diabetes mellitus (GDM) increases with increase in BMI (class I=5.4%, class II=7.6% and class III=50%). Incidence of fetal growth restriction (FGR) (7.6% and 2.7%) and post term pregnancy (38% and 16.2%) more in class II compared to class I respectively. Lower segment caesarean section (LSCS) rates are seen to be highest in class III (100%) as compared to class II (53%) and class I (50%). Class III (50%) women were more likely to have macrosomic babies than class II (40%) and class I (34.1%). Conclusions: Interventions directed towards weight loss and prevention of excessive weight gain must begin in the preconceptional period. Obese mothers must be counselled regarding risk and complications of obesity and importance of weight loss.